Ответ:
Пошаговое объяснение:
Варіант 1 .
1 . 5x + ( 3x + 3 4/2 ) + ( 2x - 4/4 ) = 5x + 3x + 5 + 2x - 1 = 10x + 4 .
2 . a ) 5x *(- 3 ) = - 15x ; коефіцієнт - 15 ;
б ) (- 4,3 )*(- х ) = 4,3х ; коефіцієнт 4,3 .
3 . а ) 4x + 5 = 3x + 7 ; б ) ( a - 2 )/3 = 2,4/1,2 ;
4x - 3x = 7 - 5 ; ( a - 2 )/3 = 2 ;
x = 2 ; a - 2 = 2 * 3 ;
a - 2 = 6 ;
a = 8 .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
Варіант 1 .
1 . 5x + ( 3x + 3 4/2 ) + ( 2x - 4/4 ) = 5x + 3x + 5 + 2x - 1 = 10x + 4 .
2 . a ) 5x *(- 3 ) = - 15x ; коефіцієнт - 15 ;
б ) (- 4,3 )*(- х ) = 4,3х ; коефіцієнт 4,3 .
3 . а ) 4x + 5 = 3x + 7 ; б ) ( a - 2 )/3 = 2,4/1,2 ;
4x - 3x = 7 - 5 ; ( a - 2 )/3 = 2 ;
x = 2 ; a - 2 = 2 * 3 ;
a - 2 = 6 ;
a = 8 .